Measuring individual differences in psychological attributes: A psychometric view of contextual effects - Buško, Vesna (Array, 2010)
This paper is meant to offer a psychometric perspective on the role of context in our understanding the behavioral and psychological phenomena. It is conceived as a short outline of the conceptual and methodological framework for the analyses of psychological instruments designed to measure theoretically more or less stable psychological attributes. The meaning of context within contemporary thoughts of test scores validity and validation process is briefly discussed. The contextual effects in psychological assessment are demonstrated within latent state-trait theoretical framework (Steyer et al., 1992 ; 1999), which follows a basic idea that measurement of any human attribute includes trait and state components, that is, depends in some systematic way on characteristics of the person, characteristics of the situation, and the interaction between person and situation.